Biotechnology : an introduction - Barnum Susan R. (Vikas publication, UK, 2003)
Biology/Zoology
UGC X PLAN (2002-2004)
ENGLISH
Keywords: Biotechnology : an introduction; Biology/Zoology; Biology/Zoology